2020
DOI: 10.1111/cdev.13424
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐Relations Between Ethnic‐Racial Discrimination and Ethnic‐Racial Identity Among Early Adolescents

Abstract: The authors examined whether the longitudinal inter‐relations between ethnic‐racial discrimination and ethnic‐racial identity vary according to the perpetrator of discrimination. The authors used three waves of data from early adolescents (n = 387; ages 11–12 at Wave 1) to assess the strength and direction of relations between perceived discrimination from non‐school adults and peers vis‐à‐vis ethnic‐racial identity exploration, commitment, private regard, and public regard. Cross‐lagged autoregressive path an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 72 publications
2
25
0
Order By: Relevance
“…Results from the present study were consistent with previous studies conducted with Asian American adolescents that found racial/ethnic discrimination to be associated with lower public regard in Chinese American, Black, and Dominican American youth of both nativity groups (i.e., born in the United States, born outside of the United States; Del Toro et al, 2021), and higher public regard in turn to be associated with lower depressive symptoms in Chinese American youth who were primarily children of immigrants (Rivas-Drake et al, 2008). Our findings build on these studies by extending the outcomes to Vietnamese American youth specifically and by demonstrating that the relationship between higher public regard and lower behavioral and emotional problems occurred for second-generation but not first-generation Vietnamese American youth, whereas the prior studies did not explore differences by nativity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Results from the present study were consistent with previous studies conducted with Asian American adolescents that found racial/ethnic discrimination to be associated with lower public regard in Chinese American, Black, and Dominican American youth of both nativity groups (i.e., born in the United States, born outside of the United States; Del Toro et al, 2021), and higher public regard in turn to be associated with lower depressive symptoms in Chinese American youth who were primarily children of immigrants (Rivas-Drake et al, 2008). Our findings build on these studies by extending the outcomes to Vietnamese American youth specifically and by demonstrating that the relationship between higher public regard and lower behavioral and emotional problems occurred for second-generation but not first-generation Vietnamese American youth, whereas the prior studies did not explore differences by nativity.…”
Section: Discussionsupporting
confidence: 92%
“…Discrimination experiences may be internalized to affect one’s private regard toward their group to negatively impact mental health outcomes (Rivas-Drake, Syed, et al, 2014). Discrimination was associated with lower private regard in Black, Dominican American, and Chinese American youth (Del Toro et al, 2021), as well as with lower ethnic-related affect in Chinese American adolescents (Hou et al, 2015). In turn, private regard was positively associated with higher self-esteem in Chinese American youth (Rivas-Drake et al, 2008) and greater levels of daily happiness in Mexican American and Chinese American adolescents (Kiang et al, 2006).…”
Section: Aspects Of Racial/ethnic Identity As Potential Paths Through...mentioning
confidence: 99%
“…Both sampling and measurement decisions in within-group designs with Black adolescents are important because they govern the prevalence, representation, and perception of Black homogeneity in the literature. Therefore, we provide sampling and measurement recommendations for researchers to consider the characteristics of their desired sample a priori, design studies to collect more detailed demographic characteristics of their sample, and report these characteristics (for examples, see Del Toro, Hughes, & Way, 2020 ; Hughes, Del Toro, Harding, Way, & Rarick, 2016 ). Sampling and measurement considerations are often intertwined.…”
Section: Recommendations For Sampling Decisions In Within-group Designsmentioning
confidence: 99%
“…Discrimination experiences during adolescence critically shape trajectories of ERS (Hughes et al, 2017;Ruck et al, 2022;Umaña-Taylor et al, 2014). When minority youth experience more discrimination, they engage in more identity exploration (Del Toro et al, 2021;Pahl & Way, 2006). Relatedly, their ethnic-racial identity becomes more central but their awareness of its negative public regard also increases (Del Toro et al, 2021;Rivas-Drake et al, 2009).…”
Section: Minority Experiences Of Discrimination and Dual Identitymentioning
confidence: 99%
“…When minority youth experience more discrimination, they engage in more identity exploration (Del Toro et al, 2021;Pahl & Way, 2006). Relatedly, their ethnic-racial identity becomes more central but their awareness of its negative public regard also increases (Del Toro et al, 2021;Rivas-Drake et al, 2009). As schools are key socialization contexts, we ask how the ERS of minority adolescents is informed by school discrimination.…”
Section: Minority Experiences Of Discrimination and Dual Identitymentioning
confidence: 99%